Penambahan Madu Dalam Pengenceran Sperma Untuk Meningkatkan Motilitas Spermatozoa, Fertilisasi dan Daya Tetas Telur Ikan Lele (Clarias sp) - Iriyanto, Adi; Watung, Julian Ch; Kalesaran, Ockstan J; Monijung, Revol D (e-Journal BUDIDAYA PERAIRAN, 2015)
The research intended to determine the optimal concentration of honey supplemented in sperm dilution to improve sperm motility, fertilization and eggs hatchability of catfish (Clarias sp). Experimental design used was a Complete Randomized Design (CRD) with four treatments each with three replications. The concentration of honey used astreatments were A (0 mL + 100 mL of physiological NaCl), B (0.60 mL + 99.40 mL of physiological NaCl), C (0.65 mL + 99.35 mL of physiological NaCl), D (0.70 mL + 99.30 mL of physiological NaCl). Parent used consisted of one female with 1.5 kg weight and the male parent with 1 kg weight.  Sperm dilution containers used was 12 plastic cups and the container fertilization and hatching eggs container used was 12 brass plates.  Spermatozoa motility observation performed immediately after dilution process. Fertilization observation was performed after 12 hours of fertilization process, and egg hatchability observation was performed after 60 hours of fertilization.  The research results showed that the addition of honey in sperm dilution contributed significant effect on spermatozoa motility, fertilization and eggs hatchability. The addition of 0.70 mL honey in sperm dilution was the best indicated by the average percentage of spermatozoa motility 83.33%, fertilization 82.50% and eggs hatchability 79.67%.   Keywords: Honey, sperm dilution, spermatozoa motility, fertilization, eggs hatchability.